Analisis Kebiasaan Membaca Buku IPA Siswa Kelas V SD Inpres 6/75 TA Kecamatan Tanete Riattang Kabupaten Bone - sudarto sudarto; Muliadi Muliadi; muhammad amran; Aminah aminah (Universtas Negeri Makassar, 2022)
The problem in this study is to describe the habit of reading science books for fifth grade students of SD Inpres 6/75 TA, Tanete Riattang District, Bone Regency. This research is a type of qualitative research with a descriptive method that describes the habit of reading science books for fifth grade students which includes reading time, reading time, reading place, reading position, taking notes or not taking notes on important things from reading, scheduled, reading in a quiet or crowded atmosphere. , summarize the contents of the reading, and use the school library in reading activities. From the results of this study, it can be said that the habit of reading science books for fifth grade students is fairly good. However, there are still some students who do not have a good habit of reading science books from the description of reading habits, such as, not making good use of the library as a place to read and not taking notes on important things from what they read. So there are some students who do not have good reading habits. Keywords: Habits; Read; natural Science